Hubungan antara Konformitas Terhadap Teman Sebaya dengan Perilaku Bullying pada Siswa SMPN 22 - Novianty, Lola; Putra, Denny (Noetic Psychology, 2014)
AbstractPeer pressure in adolescent is a common issue that can give positive and negative impact. Among the negative impact of peer pressure is bullying behavior. Bullying behavior isÃÂ  repeated verbal, physical, social or psychological aggressive behaviour by a person or group directed towards a less powerful that is intended to cause harm, distress or fear.ÃÂ  This research aim to explore the relationship between bullying and conformity among junior high school student in SMPN 22 Tangerang. Bullying behavior was measured using bullying behaviour scale, and conformity was measured using comformity scale (Rahmwati, 2014). The result showed that there were a non significance and positive correlation between bullying and conformity (r = 0,224, p = 0,025 < 0,05). ÃÂ Kata kunci: Konformitas terhadap teman sebaya, perilaku bullying, siswa SMPÃÂ